Death of a child and the risk of heart failure: a population-based cohort study from Denmark and Sweden. (14th October 2021) - Wei, D; Li, J; Chen, H; Janszky, I; Ljung, R; Fang, F; Laszlo, K.D
Abstract: Background: Increasing evidence suggests that the death of a child is associated with increased risks of ischemic heart diseases and atrial fibrillation and the association is in part attributable to stress-related mechanisms. However, knowledge regarding the risk of heart failure (HF) after the death of a child is very limited. Purpose: To study the association between the death of a child and the parents' risk of HF. Methods: We conducted a population-based cohort study involving parents of live-born children recorded in the Danish and Swedish Medical Birth Registers during 1973–2016 and 1973–2014, respectively (n=6, 717, 531). We retrieved information on child death, HF diagnosis and parents' sociodemographic characteristics from several nationwide registries. We performed Poisson regression models to estimate incidence rate ratio (IRR) and 95% confidence intervals (CI) for HF. Results: A total of 129, 829 (1.9%) parents lost at least one child during the follow-up. Bereaved parents had a 35% higher risk of HF than non-bereaved parents [IRR (95% CI): 1.35 (1.29–1.41)]. The association was present not only if the child died due to cardiovascular or other natural causes [IRR (95% CI): 1.48 (1.25–1.75) and 1.35 (1.27–1.44), respectively], but also in case of unnatural deaths [IRR (95% CI): 1.32 (1.24–1.42)]. There was a trend toward a U-shaped association according to the deceased child's age at loss and the risk of HF. Bereaved parents who lost their only child or had three or more remaining live children at the time of loss had higher HF risk than those with one or two live children at the time of loss. We found no clear evidence for a difference in the association of interest over time. Conclusions: The death of a child was associated with an increased risk of HF. The finding that not only cardiovascular and other natural deaths, but also unnatural deaths were associated with HF suggests that stress-related mechanisms may contribute to the development of HF. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Swedish Council for Working Life and Social Research and Karolinska Institutet's Research Foundation